Self-injurious behaviour in patients with anorexia nervosa: a quantitative study - Linda Smithuis; Nienke Kool-Goudzwaard; Janneke M. de Man-van Ginkel; Harmieke van Os-Medendorp; Tamara Berends; Alexandra Dingemans; Laurence Claes; Annemarie A. van Elburg; Berno van Meijel (Journal of Eating Disorders, 2018)
Abstract Background Many patients with an eating disorder report difficulties in regulating their emotions and show a high prevalence of self-injurious behaviour. Several studies have stated that both eating disorder and self-injurious behaviour help emotion regulation, and are thus used as coping mechanisms for these patients. We aimed to determine the prevalence of self-injurious behaviour, its characteristics and its emotion-regulation function in patients with anorexia nervosa or an eating disorder not otherwise specified (n = 136). Methods A cross-sectional design using a self-report questionnaire. Mann–Whitney U-tests were conducted to compare the background and clinical variables between patients with self-injurious behaviour and patients without this type of behaviour. Changes in emotional state before and after self-injurious behaviour were tested by Wilcoxon signed rank tests. Results Our results showed a 41% prevalence of self-injurious behaviour in the previous month. Patients who performed self-injurious behaviour had a statistically significant longer treatment history for their eating disorder than those who did not. Whereas 55% of self-injuring patients had a secondary psychiatric diagnosis, only 21% of participants without self-injurious behaviour did. Regarding the impact of self-injurious behaviour, our results showed a significant increase in “feeling relieved” and a significant decrease in “feeling angry at myself”, “feeling anxious” and “feeling angry at others”. This indicates that self-injurious behaviour can be regarded as an emotion-regulation behaviour. Participants were usually aware of the causes of their self-injurious behaviour acts. Conclusions Professionals should systematically assess the occurrence of self-injurious behaviour in eating disorder patients, pay special attention to patients with more severe and comorbid psychopathology, and those with a long treatment history. This assessment should be followed by a functional analysis of the self-injurious behaviour and by effective therapeutic interventions alongside the eating disorder treatment.